Pengamanan Data Arsip Pada Balai Desa Sidodadi Menggunakan Kriptografi Modern RC4 - Khairul Fahmi (STMIK Budi Darma, 2021)
The issue of data security and confidentiality is very important at the Village Hall. The Village Hall has many confidential documents such as population data and other data. Confidential documents or data should not be known by outside parties because they can cause harm to village officials and government. To secure the data, the RC4 algorithm is used. The RC4 algorithm was chosen because the processing time is faster than other algorithms. The RC4 algorithm uses two Substitution Boxes (S-Box), namely an array of 256 lengths containing permutations from 0 to 255, and the second S-Box containing permutations is a function of a variable length key.Cryptography